2008
DOI: 10.4103/0250-474x.40325
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vivo</i> evaluation of single dose tetanus toxoid vaccine formulation with chitosan microspheres

Abstract: Chitosan adsorbed microspheres containing tetanus toxoid were prepared in the size range of 10 μm to 75 μm, by emulsion-cross linking technique at different speeds of agitation. The amount of tetanus toxoid incorporated into chitosan microspheres were estimated by limes flocculation test and in vivo evaluation of tetanus toxoid adsorbed chitosan microspheres were determined by toxin neutralization method using albino mice. The results of in vivo release for the batches of 10 μm and 25 μm correlates with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
2
2
1
Order By: Relevance
“…The presence of flocculation found after 14 ± 0.5 min indicated that the sample was stable. Similar results were obtained for tetanus toxoid vaccine formulation with chitosan microspheres in earlier study [45].…”
Section: Flocculation Test Resultssupporting
confidence: 90%
“…The presence of flocculation found after 14 ± 0.5 min indicated that the sample was stable. Similar results were obtained for tetanus toxoid vaccine formulation with chitosan microspheres in earlier study [45].…”
Section: Flocculation Test Resultssupporting
confidence: 90%
“…The tetanus toxoid was good at boosting the humoral immune response and inducing antibody production which agrees with the report of Manivannan et al (2008) and Li et al (2012). The highest values of flocculation limit were reported when CFA was administered with toxoid compared to the IFA group.…”
Section: Discussionsupporting
confidence: 89%
“…However, for the tetanus toxoid encapsulation within chitosan microspheres cross-linking associated to emulsion techniques was used. The result achieved was 70e84% of efficiency, which was determined through the time flocculation test procedure [18]. However, high efficiency was obtained through encapsulation techniques and efficiency evaluation very different from those applied on the present study.…”
Section: Discussioncontrasting
confidence: 54%